Real-time PCR detection and quantification of fish probiotic Phaeobacter strain 27-4 and fish pathogenic Vibrio in microalgae, rotifer, Artemia and first feeding turbot (Psetta maxima) larvae - Prol García, María Jesús; Bruhn, J. B.; Pintado, José; Gram, Lone (Journal of Applied Microbiology, 2009)
12 páginas, 5 tablas, 1 figura Aims: To develop a SYBR Green quantitative real-time PCR protocol enabling detection and quantification of a fish probiotic and two turbot pathogenic Vibrio spp. in microcosms. Methods and Results: Phaeobacter 27-4, Vibrio anguillarum 90-11-287 and Vibrio splendidus DMC-1 were quantified as pure and mixed cultures and in presence of microalgae (Isochrysis galbana), rotifers (Brachionus plicatilis), Artemia nauplii or turbot (Psetta maxima) larvae by real-time PCR based on primers directed at genetic loci coding for antagonistic and virulence-related functions respectively. The optimized protocol was used to study bioencapsulation and maintenance of the probiont and pathogens in rotifers and for the detection and quantification of Phaeobacter and V. anguillarum in turbot larvae fed rotifers loaded with the different bacteria in a challenge trial. Conclusions: Our real-time PCR protocol is reproducible and specific. The method requires separate standard curve for each host organism and can be used to detect and quantify probiotic Phaeobacter and pathogenic Vibrio bioencapsulated in rotifers and in turbot larvae. Significance and Impact of the Study: Our method allows monitoring and quantification of a turbot larvae probiotic bacteria and turbot pathogenic vibrios in in vivo trials and will be useful tools for detecting the bacteria in industrial rearing units María J. Prol is granted by I3 Program from CSIC that is co-financed by European Social Fund. Funding was provided by INIA (ACU03-003) and I3 Program from the Spanish Ministry of Education and Science (PIE 2006 7 01067). Peer reviewed